An overview on extraction, composition, bioactivity and food applications of peanut phenolics. (1st July 2022) - Bodoira, Romina; Cecilia Cittadini, M.; Velez, Alexis; Rossi, Yanina; Montenegro, Mariana; Martínez, Marcela; Maestri, Damián
Graphical abstract: Highlights: The peanut skin (PS) contains a vast array of phenolic compounds. PS phenolics can be properly obtained by means of green extraction technologies. PS phenolics can display diverse antioxidant activities in food and biological systems. PS phenolics can make a meaningful contribution to food preservation. Obtaining stable, product-specific compositions is a priority for future research. Abstract: Peanuts contain a diverse and vast array of phenolic compounds having important biological properties. They are allocated mostly in the seed coat (skin), an industrial waste with minor and undervalued applications. In the last few years, a considerable amount of scientific knowledge about extraction, composition, bioactivities and health benefits of peanut skin phenolics has been generated. The present review was focused on four main aspects: a) extraction methods and technologies for obtaining peanut skin phenolics with an emphasis on green-solvent extraction processes; b) variations in chemical profiles including those due to genetic variability, extraction methodologies and process-related issues; c) bioactive properties, especially antioxidant activities in food and biological systems; d) update of promising food applications. The revision was also aimed at identifying areas where knowledge is insufficient and to set priorities for further research.